Pengaruh Serai (Cymbopogon Citratus) Terhadap Penurunan Nyeri Gout Athritis pada Masyarakat di Kelurahan Winenet Satu Kota Bitung - Rahmat Ismail; Agust A. Laya (Pusat riset dan Inovasi Nasional, 2023)
People with gout arthritis complain of pain in the joints, toes, hands, knees and have never used lemongrass water to reduce joint pain and choose analgesic drugs as pain relief. Lemongrass plant contains essential oil that has chemical properties and pharmacological effects, namely a spicy and warm taste as an anti- inflammatory and relieving analgesic pain.. The purpose of this research was to find out the effect of lemongrass (cymbopogon citratus) on the reduction of gout arthritis pain in The Community In The 1st Winenet Village, Bitung. This research used a pre experimental method with one group pretest-posttest design. The population were residents who suffered from gout arthritis and who experienced joint pain. Sampling using a purposive sampling technique with the number of samples were 12 respondents using the Lamesho formula. The instruments used in this research were observation sheets and pain intensity scale measurement sheets using the Numeric Rating Scale (NRS). The collected data was processed by running the computer program be analyzed by a Wilcoxon Signed Rank test with the significance level α = 0,05.The results of this research indicated that there are differences in pain intensity before and after giving lemongrass, with a ρ value (0,001) < (0,05), meaning that there is an effect of giving lemongrass on reducing gout arthritis pain.The conclusion of this research is that lemongrass can be used as a non- pharmacological therapy to reduce pain in gout arthritis. It is expected that the result of this research will be useful in reducing pain in patients with gout arthritis and can be used as an additional reference for further research.